Transport Corridors in the Russian Integration Projects, the Case of the Eurasian Economic Union - O. A. Podberezkina (Vestnik MGIMO-Universiteta)
The article discusses the political importance of transport corridors in terms of the development of integration projects in the post-Soviet space. The world is witnessing the formation of a single market and transport and communication infrastructure, which intensifies competition among regional and world leaders, both states and non-state actors, such as businesses, markets over the routes of transporting goods. In the medium and long term the value of the control over the transport routes will increase due to the dynamics of economic development in the Asia-Pacific region. Competition for the development of projects of international transport corridors (ITC) between the leading countries in the region will increase, because the ITC entail the formation of a common political space, the reduction of tariff and customs barriers, which provides easy access to the markets of countries linked by ITCs and creates the preconditions for economic integration. The growing political importance of ITC is reflected in the fact that global leaders such as China, the US, the EU, are trying to create their own versions of international land transport corridors connecting Europe and Asia. China is trying to promote their transport project "Economic Belt Silk Road" European countries develop cooperation on ITC TRACECA with other countries of Eurasia. US also embody their interests through the implementation of the project by the ITC in Afghanistan. Transport corridors in Russia are seen as a way to integrate it into the global transportation system and logistics space. To do this, Russia needs to develop Eurasian transport corridors through its territory. As a result of the implementation of transport projects Russia will be able to ensure the transit of goods from China to Europe, which has a positive impact on the economic development of the regions through which they pass. Development of international transportation through Russia will unite many of the players on the world stage: integration associations, state, transnational corporations, business entities, regional authorities.